Execution of Management Curriculum Private Universities in Four Management Functions - ., Mudzakir; Tahwin, Muhammad (International Journal of Engineering and Technology, 2018)
The study design consists of stages: (1) a preliminary study (identification of potential and problems, collection of data, literature and research results relevant), (2) the manufacture of product design (development of a model curriculum management-oriented soft skills of students), (3 ) validation of products or internal validation (FGD, validation experts and practitioners), and (4) test the feasibility of the product (external validation). The purpose of education in an educational process that is planned and organized in an educational program called the curriculum and consists of: (1) curriculum plan as a document in the form of details of courses, syllabus, learning design, system evaluation of learning, and (2) actual curriculum as a implementation of the program in the form of learning that is manifestly conducted. Data analysis techniques in the preliminary study used interactive analysis techniques with the steps: (1) collect the data, (2) data reduction, (3) presentation of data, and (4) conclusion. Data analysis techniques in the development and validation of internal models using qualitative analysis techniques. For the data from the test results that the expanded use of descriptive statistical analysis techniques. Education in the principles of economics resulted in: (1) output as indicated by academic and non academic achievement, repetition rate, and dropout rates, and (2) the outcome indicated with opportunities for education, employment, and self-development. Education as a concerted effort through a learning process with a conducive environment so as to change attitudes and behavior, develop skills and character development, as well as active learners can develop their potential.Â